Surface modified receptor mediated delivery systems for site specific treatment of cancer - Vanapariya, Fenil; Malviya, Miteshkumar; Nathabhai, Shiroya Milankumar (Creative Pharma Assent, 2021)
The treatment of the cancer has many challenges now a days due to side effects of the treatment. However, in the modern formulation development the concept of the site specific drug delivery for disease treatment in the body is considering as continuous challenges. Observing the challenges in convectional technique site specific drug delivery system has good potential to reduce adverse side effects, efficiently improve the human body health with very low toxicity. This review article elaborates the current challenges and prospective of surface modified drug carrier systems for delivery of protein for site-specific treatment of cancer and anti-cancer drug.